A Proposed TEV Framework for Pulau Payar Marine Park (Journal of Business Management and Accounting, 2017)
This paper aims to propose Total Economic Value (TEV) framework for Pulau Payar Marine Park (PPMP). Currently, TEV framework for PPMP revealed a few components despite infeasibility of certain main scientific data to be acquired and also under assumption of non-climate change phenomenon. With the MPA exposures towards recent climate change phenomenon, this paper explored the extended areas in Pulau Payar that might contribute either positively or negatively to the value of the PPMP which will assist in marine park management in their policy making. This study conducted along the qualitative paths in which information are gathered through focus group discussions and empirical study relevant to the calamity of coral bleaching. The findings illustrate that there are eight (8) items would contribute to the use and non-use value of the TEV framework.